Effect of phosphorus content on Cu/Ni-P/Sn-3.5Ag solder joint strength after multiple reflows - Mona, M. (2013)
Electroless Ni-P layers with three different P contents (6.1 wt.%, 8.8 wt.%, and 12.3wt.%) were deposited on copper (Cu) substrates. Multilayered samples of Sn-3.5Ag/Ni-P/Cu stack were prepared and subjected to multiple reflows at 250°C. A tensile test was performed to investigate the effect of P content on the solder joint strength. The low P samples exhibited the highest joint strength after multiple reflows, while the strength of medium and high P samples decreased more rapidly. From interfacial analysis, the Ni3Sn4 intermetallic compound (IMC) formed at the interface of low P sample was found to be more stable, while the one of medium and high P samples spalled into the molten solder. The IMC spallation sped up the consumption of electroless Ni-P, leading to the large formation of Cu-Sn IMCs. Fractographic and microstructural analyses showed that the degradation in solder joint strength was due to the formation of layers of voids and growth of Cu-Sn IMCs between the solder and the Cu substrate.